Law and religion in the Commonwealth the evolution of case law - Foster, Neil; Babie, Paul 1966-; Barker, Renae (London [England] Hart Publishing, 2022)
"This book examines law and religion from the perspective of its case law. Each chapter focuses on a specific case from a Commonwealth jurisdiction, examining the history and impact of the case, both within the originating jurisdiction and its wider global context. The book contains chapters from leading and emerging scholars from across the Commonwealth, including from the United Kingdom, Canada, Australia, Pakistan, Malaysia, India and Nigeria. The cases are divided into four sections covering: - Foundational Questions in Law and Religion - Freedom of Religion around the Commonwealth - Religion and state relations around the Commonwealth - Rights, Relationships and Religion around the Commonwealth. Like religion itself, the case law covers a wide spectrum of life. This diversity is reflected in the cases covered in this book, which include: - Titular Roman Catholic Archbishop of Kuala Lumpur v Home Minister on the use of Allah by non-Muslims in Malaysia - The Church of the New Faith v Commissioner of Pay-roll Tax (Vic) which determined the meaning of religion in Australia - Eweida v UK which clarified the application of Article 9 of the European Convention on Human Rights - R v Big M Drug Mart on the individual protections of religious freedom under the Canadian Charter of Rights. The book examines how legal disputes involving religion are among the most contested in the courts and shows that in these cases, passions run high and the outcomes can have significant consequences for all involved."--
1. Introduction Renae Barker, Paul Babie and Neil Foster Part I: Foundational Questions in Law and Religion -- 2. The Scientology Case: Defining Religion for the World (Australia) Renae Barker -- 3. The Allah Case: What is the Name of God? (Malaysia) Joshua Neoh Part II: Freedom of Religion around the Commonwealth -- 4. Cross Words: Eweida v UK and Reformulation of Religious Freedom (UK) Russell Sandberg -- 5. Crumbs of Comfort in the Culture Wars: The 'Gay Cake' Case (UK) Ian Leigh -- 6. R v Big M Drug Mart (Canada) Richard Moon -- 7. Shalla v State: On Blasphemy and Blasphemy Laws in Islam (Nigeria) Azizat Omotoyosi Amoloye-Adebayo and Imam-tamim Muhammad kamaldeen -- 8. Indira Gandhi v Pengarah Jabatan Agama Islam Perak (Malaysia) Dian AH Shah Part III: Religion and State Relations around the Commonwealth -- 9. Aston Cantlow v Wallbank: Defining the Public and Private Functions of the Established Church of England (UK) Mark Hill QC -- 10. The Defence of Government Schools Case: Establishing a Dog's Breakfast? (Australia) Luke Beck -- 11. Adelaide Company of Jehovah's Witnesses Inc v Commonwealth (Australia) Paul Babie -- 12. Ayodhya Judgment (M Siddiq (D) Thr Lrs Vs. Mahant Suresh Dass & Others) (India) Sawinder Singh -- 13. Benazir Bhutto vs. Federation of Pakistan (Pakistan) Umar Rashid Part IV: Rights, Relationships and Religion around the Commonwealth -- 14. The Legal Status of Religious Marriage in the UK: Attorney General v Akhter & ors (UK) Michelle Flynn -- 15. Christian Youth Camps ltd v Cobaw Community Health Services Ltd (Australia) Neil Foster -- 16. Shabarimala (Indian Young Lawyers Association) & Ors v The State of Kerala & Ors in Writ Petition & Shayara Banu (Shayara Bano) v Union of India and Others (India) Preeti Nalavadi -- 17. Allcard v Skinner (1887) 36 Ch D 145 Craig Allen
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Religion And Law -- Commonwealth countries; Religion and state -- Commonwealth countries; Freedom Of Religion -- Commonwealth countries